Comparative morphology of the mouthparts of weevils of the subfamily Curculioninae (Coleoptera, Curculionidae) - Kurbatov, Sergey A. (Zootaxa, 2025)
The mouthparts of 57 mainly Palaearctic species of the subfamily Curculioninae, belonging to 41 genera of 17 tribes, are studied and illustrated. Descriptions of various characters of mandibles, maxillae and labia of the mentioned taxonomic group are given. The conformity of the structure of mouthparts to the accepted taxonomic pattern of the studied taxa is evaluated.